1. Effect of Compensatory Growth on Performance of Sudanese Female Goats - Yagoub, Yagoub M.; Babiker, Salih Ahmed (Pakistan Journal of Nutrition, 2009)
Tow groups of female goats less than one year in age, Nubian ecotype (15 goat/group) and of the same initial weight (16.5 kg/kid) were subjected to tow dietary levels of energy for 105 days, the first group was offered the highest energy diet (11.5 MjME/kcl) while the second group was given the lowest dietary energy diet (8.5 MjME/kcl). Through this term of the experiment (105 days) goats of the second group were found just to maintain their weight. Then seven goats from the second group was offered the highest energy diet (11.5 MjM E/kg) to reach the final weight obtained by the first group, it spent 175 days to reach that weight. These goats which were raised on the lowest dietary energy level (8.5 MjME/kg) were used to study the effect of compensatory growth on the performance of Sudanese female goats. Weekly, daily rate of gains and total dry matter intake were significantly (p< 0.001) lower in the compensating female goats than the first group.It could be concluded that compensatory growth significantly (p<0.01) affected daily and weekly rate of gain and total dry matter intake which were lower in the compensating goats than the normally growing goats.